Sex steroid and cognitive function among community-dwelling older men with or without vascular risk factors: a cross-sectional study - Shuning Tang; Limei Huang; Fangting Lin; Xiuqin Chen; Yunhui Wang; Jixiang Xu; Yujie Wang; Junling Gao; Qianyi Xiao (BMC Geriatrics, 2024)
Abstract Background The relationship of testosterone and estradiol concentrations with cognitive function among community-dwelling older men was inconclusive. To examine the association of serum testosterone and estradiol concentrations with cognitive function in older men with or without vascular risk factors (VRFs). Methods This cross-sectional study consisted of 224 community-dwelling men aged 65–90 years in the Songjiang District of Shanghai, China. Serum testosterone and estradiol were measured by electrochemiluminescence immunoassay. The following five factors were defined as VRFs in this study: obesity, history of hypertension, diabetes, stroke, and coronary heart disease. Multivariable linear regression was used to examine the association of testosterone and estradiol with the Mini-Mental State Examination (MMSE) in participants with or without VRF. Restricted cubic spline (RCS) regression was performed to account for the nonlinearity of these associations. Results An inverted “U” shaped non-linear relationship was found between testosterone concentration and MMSE score in men with one VRF (P overall =.003, non-linear P =.002). Estradiol showed an inverted “U” shaped non-linear relationship with MMSE score independent of VRFs (men without VRF, P overall =.049, non-linear P =.015; men with one VRF, overall P =.007, non-linear P =.003; men with two or more VRFs, overall P =.009, non-linear P =.005). Conclusion In older men, an optimal level of sex steroid concentration may be beneficial to cognitive function and the VRFs should be considered when interpreting the relationship between sex steroid and cognitive function.